Dynamics of COVID-19 Development: New Data and New Estimates from Wavelet Analysis - Lyashenko, V. (AMRS, 2020)
Investigation of the dynamics of diseases from viruses is a key issue in the understanding of their distribution. This is especially important when viruses are dangerous. This requires the use of various analysis tools. We used wavelet coherence. We obtained results that explain some of the dynamics of the COVID-19 pandemic. We also conducted a comparative analysis of the development of the pandemic between individual European countries.
Keywords: COVID-19; wavelet coherence